2009
DOI: 10.1590/s0100-736x2009001100008
|View full text |Cite
|
Sign up to set email alerts
|

Inefficacy of albendazole sulphoxide and ivermectin for the treatment of bovine parasitic otitis caused by rhabditiform nematodes

Abstract: 910Pesq. Vet. Bras. 29(11):910-912, novembro 2009 RESUMO.-[Ineficácia do sulfóxido de albendazole e da ivermectina no tratamento da otite parasitária bovina causada por nematóides rhabditiformes.] O objetivo deste estudo foi avaliar a eficácia do sulfóxido de albendazol administrado oralmente e da ivermectina "pour-on" no tratamento da otite parasitária bovina causada por nematóides rhabditiformes. Dezoito vacas Gir apresentando otite clínica foram divididas em três grupos de seis animais cada. O primeiro n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
2
0
5
Order By: Relevance
“…Ivermectin has been found to be effective at killing C. bovis and in the treatment of bovine parasitic otitis in cattle in Tanzania [50]. In contrast, similar studies have found ivermectin and albendazole to be an ineffective treatment for bovine parasitic otitis in cattle in Brazil [51,52]. Aside from P-glycoproteins, FAR proteins, galectins, and serpins are known to be actively secreted by several parasitic nematode species, and an immunomodulatory role has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Ivermectin has been found to be effective at killing C. bovis and in the treatment of bovine parasitic otitis in cattle in Tanzania [50]. In contrast, similar studies have found ivermectin and albendazole to be an ineffective treatment for bovine parasitic otitis in cattle in Brazil [51,52]. Aside from P-glycoproteins, FAR proteins, galectins, and serpins are known to be actively secreted by several parasitic nematode species, and an immunomodulatory role has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Some treatments for the otitis are available; however, all without satisfactory results, explained by its constant recurrence, ineffectiveness or costs and even the operational impossibility of methods employed (Leite et al 1994, Vieira et al 1998, Verocai et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Apenas 20% (2/10) dos bovinos foram negativos em duas coletas com o uso da ivermectina. Resultados ineficientes com o uso desta droga na concen- tração de 0,5% foram também relatados por Verocai et al (2009). Diante dos dados obtidos, a ineficiência desta droga no combate a estes parasitas possivelmente pode estar relacionada com a resistência destes ao produto usado, ou que seria necessário o uso da droga em concentrações mais elevadas.…”
Section: Resultsunclassified